Cryptic speciation within Asthenodipsas vertebralis (Boulenger, 1900) (Squamata: Pareatidae), the description of a new species from Peninsular Malaysia, and the resurrection of A. tropidonotus (Lidth de Jude, 1923) from Sumatra: an integrative taxonomic analysis - Loredo, Ariel I.; Wood, Perry Jr. L.; Quah, Evan S. H.; Anuar, Shahrul; Greer, Lee F.; Ahmad, Norhayati; Grismer, Lee (Zootaxa, 2013)
A review of the taxonomic status of the Asian Slug Snake, Asthenodipsas vertebralis (Boulenger, 1900) based on an in-tegrative taxonomic approach using molecular, morphological, color pattern, and ecological data indicate it is composed of three well supported monophyletic lineages: (1) Pulau Tioman and Fraser’s Hill, Pahang and Bukit Larut, Perak; Pen-insular Malaysia; (2) its sister lineage from Northern Sumatra; and (3) the remaining basal lineage from Peninsular Ma-laysia. Furthermore, we consider the high sequence divergence (6.3%–10.2%) between these lineages (especially in areas of sympatry) and discrete differences in their morphology, color pattern, and microhabitat preference as evidence they are not conspecific. As such, we resurrect the name A. tropidonotus (Lidth de Jeude, 1923) for the Sumatra populations, re-strict the name A. vertebralis to the populations from Pulau Tioman, Genting Highlands, Fraser’s Hill, Gunung Benom, and Bukit Larut that contain terrestrial, banded adults; and consider A. lasgalenensis sp. nov. to be restricted to the pop-ulations from Fraser’s Hill, Cameron Highlands, and Bukit Larut that contain arboreal, unbanded adults.